2022
DOI: 10.1051/0004-6361/202244293
|View full text |Cite
|
Sign up to set email alerts
|

HD 23472: a multi-planetary system with three super-Earths and two potential super-Mercuries,

Abstract: Context. Comparing the properties of planets orbiting the same host star, and thus formed from the same accretion disc, helps in constraining theories of exoplanet formation and evolution. As a result, the scientific interest in multi-planetary systems is growing with the increasing number of detections of planetary companions. Aims. We report the characterisation of a multi-planetary system composed of five exoplanets orbiting the K-dwarf HD 23472 (TOI-174). Methods. In addition to the two super-Earths that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 152 publications
0
7
0
Order By: Relevance
“…In other words, we might expect the innermost planets in multiplanet systems to be more iron-rich than their outer siblings. For instance, Barros et al (2022) characterized the HD 23472 system, which contains 5 small planets orbiting a K-dwarf, and they found a clear decrease in the core mass fractions of the planets with increasing period. Similarly, they found that the water and gas mass fraction increases as a function of the period such that the innermost planets are dry and dense and the outermost ones have much larger fractions of water and gas.…”
Section: Planetary Core/water Mass Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, we might expect the innermost planets in multiplanet systems to be more iron-rich than their outer siblings. For instance, Barros et al (2022) characterized the HD 23472 system, which contains 5 small planets orbiting a K-dwarf, and they found a clear decrease in the core mass fractions of the planets with increasing period. Similarly, they found that the water and gas mass fraction increases as a function of the period such that the innermost planets are dry and dense and the outermost ones have much larger fractions of water and gas.…”
Section: Planetary Core/water Mass Fractionsmentioning
confidence: 99%
“…These ultra-dense planets could be super Mercuries (see, e.g.,Santerne et al 2018;Adibekyan et al 2021;Schulze et al 2021;Rodríguez Martínez et al 2023, andBarros et al 2022), but they have relatively large mass uncertainties so more observations are needed to robustly determine their composition. 9 K2-18 c has been recently validated byRadica & Artigau (2022), however, we do not include it in our analysis as it does not have a radius measurement.…”
mentioning
confidence: 99%
“…Of more than 5300 confirmed exoplanets 18 , there are 66 sub-Neptune sized planets (1.75 < R P / R ⊕ < 3.5) transiting bright stars (G ≤ 10 mag). Only 18 of these have an insolation flux less than HD 15906 b and only 5 have an insolation flux lower than HD 15906 c -GJ 143 b (Dragomir et al 2019), 𝜈 2 Lupi d (Delrez et al 2021), HD 23472 c (Barros et al 2022), HD 73583 c (Barragán et al 2022) and Kepler-37 d (Marcy et al 2014). HD 15906 c is therefore one of the most lowly irradiated sub-Neptune planets transiting such a bright star.…”
Section: Comparison With Confirmed Exoplanetsmentioning
confidence: 96%
“…HD 15906 c is therefore one of the most lowly irradiated sub-Neptune planets transiting such a bright star. Furthermore, there are only 5 other multiplanet systems with two warm (T eq ≤ 700 K) sub-Neptune sized planets (1.75 < R P / R ⊕ < 3.5) transiting a bright (G ≤ 10 mag) star -HD 108236 (Bonfanti et al 2021), 𝜈 2 Lupi (Delrez et al 2021), HD 191939 (Orell-Miquel et al 2023, HD 23472 (Barros et al 2022) and TOI 2076 . The HD 15906 system is therefore an interesting target for future follow-up studies, discussed further in Section 7.4.…”
Section: Comparison With Confirmed Exoplanetsmentioning
confidence: 99%
“…Without the context of hosting an S-type planet, DMPP-3AB is not a particularly close binary, but it is the most compact binary system to harbour an S-type planet observed thus far. It is also one of the few systems containing a radial velocity (RV) detected S-type super-Earth around an FGK star (B20; Unger et al 2021;Barros et al 2022). Su et al (2021) compare the known S-type RV discoveries, and show that DMPP-3A b is an extreme outlier in their sample.…”
Section: Introductionmentioning
confidence: 98%